(3RgQ GdceGe aj bUI jhSa Ydjg GdSdGes - (3YeQ Hf EHQGgje Hf YeQ, SQGL GdOjf, CHh MaU GdCfUGQj GdChSj GdoerQSj,J (B751 (3g` s ((3CMeO Hf eMeO Hf eMeO GdCSOi s)
(3ChdgG (B:s
(3GdMeO ddg cKjQkG GYdehG QMece Gddg Cf bUU GdCfHjGA Ydjge GdSdGe YXI def SeYgG s
(3BNQgG (B:s
(3aLfGHg QMH eDed hgh GdEdg GdhGMO GdbgGQ s
(3GfXQ Qbe (B1092 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B39s
Keywords: (3GdJGQjNs